Roman Pollak – współtwórca oddziału Towarzystwa Dante Alighieri w Poznaniu (1927–1939) - Henczel, Ligia (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
As an attempt at presenting the social work of professor Roman Pollak in the interwar period, this article provides an analysis of the documents held by the Polish-Italian cultural organisation Polonia-Italia in Poznań. What emerges is an image of an exceptionally active person, well-organised and driven by the constant will to pass on the knowledge of Poland’s and Italy’s cultural legacy by means of scientific, publishing and popularising initiatives.